Struktur Penalaran Kolom Opini dalam Surat Kabar dan Pemanfaatannya sebagai Pengembangan Bahan Ajar Menulis Teks Eksposisi - Perwitasari, Wahyu Rahmalia; Kurniawan, Khaerudin (MASALIQ, 2023)
This study aims to analyze the pattern of paragraph reasoning found in national newspapers to be used as a guide for students in writing texts valid and quality exposition in terms of reasoning. These include, a) the structure of reasoning in opinion texts, b) variations of reasoning in opinion texts, and c) the benefits of reasoning in opinion texts as teaching materials for writing exposition texts. This research design uses a qualitative method with a narrative study. Opinion texts used as data sources in this study are opinion texts published in the newspapers Kompas, Media Indonesia and Sindo.. The results of this study are, a) the structure of reasoning contained in each of these newspapers, which consists of establishment, proof, and conclusion; b) the variations of reasoning found in the three newspapers include Sindo having 33 deductive reasoning, 16 inductive reasoning, 4 inerative reasoning, and 3 mixed reasoning; Kompas which has 40 paragraphs with deductive reasoning, 11 inductive reasoning patterns, 4 mixed reasoning patterns, and 1 inerative paragraph reasoning pattern; and Media Indonesia which has a total of 44 deductive reasoning patterns, 10 inductive reasoning paragraph patterns, 4 paragraphs with mixed reasoning patterns, and 4 paragraphs with inerative reasoning patterns c) reasoning in opinion texts in national newspapers can be used as a supplement to exposition text teaching materials in learning Indonesian at the senior high school level in class X in KD 4.4.